Motion-robust cardiac B1+ mapping at 3T using interleaved bloch-siegert shifts - Weingärtner, Sebastian (Magnetic resonance in medicine, 2017)
Purpose To develop and evaluate a robust motion-insensitive Bloch-Siegert shift based mapping method in the heart. Methods Cardiac Bloch-Siegert mapping was performed with interleaved positive and negative off-resonance shifts and diastolic spoiled gradient echo imaging in 12 heartbeats. Numerical simulations were performed to study the impact of respiratory motion. The method was compared with three-dimensional (3D) actual flip angle imaging (AFI) and two-dimensional (2D) saturated double angle method (SDAM) in phantom scans. Cardiac maps of three different views were acquired in six healthy volunteers using Bloch-Siegert and SDAM during breath-hold and free breathing. In vivo maps were evaluated for inter-view consistency using the correlation coefficients of the profiles along the lines of intersection between the views. Results For the Bloch-Siegert sequence, numerical simulations indicated high similarity between breath-hold and free breathing scans, and phantom results indicated low deviation from the 3D AFI reference (normalized root mean square error [NRMSE] = 2.0%). Increased deviation was observed with 2D SDAM (NRMSE = 5.0%) due to underestimation caused by imperfect excitation slice profiles. Breath-hold and free breathing Bloch-Siegert in vivo maps were visually comparable with no significant difference in the inter-view consistency (P > 0.36). SDAM showed strongly impaired map quality during free breathing. Inter-view consistency was significantly lower than with the Bloch-Siegert method (breath-hold: P = 0.014, free breathing: P < 0.0001). Conclusion The proposed interleaved Bloch-Siegert sequence enables cardiac mapping with improved inter-view consistency and high resilience to respiratory motion.